Faculty Development: Social Representations Constructed by Medical School Teachers - Almeida,Maria Tereza Carvalho (2019)
ABSTRACT Faculty Development seeks to support educators in a range of functions in the areas of teaching, research, extension, management and evaluation. The aim of this study was to evaluate faculty development based on the social representations constructed by the teachers of a medical course. A qualitative survey was carried out, using the analytical method of discourse analysis and social representation as a theoretical contribution. Twelve teachers were randomly selected, and a semi-structured interview was conducted for the data collection. The responses, recorded in audio, were transcribed and discourse analysis was performed with the aim of mapping the social representations constructed by the subjects. The social representations were grouped into two categories: institutional development and personal development. Within the category institutional development, three subcategories were identified: Guiding principles of Faculty Development Programs, Teaching-learning strategies used in Faculty Development Programs, and Skills to be developed by faculty. Within the category Personal development, two subcategories were identified: Development as a person and as a social being, and Professional development. Over the years, a variety of social representations have been constructed in relation to the nature of teaching in medical education, but it is only in recent decades that managers and teachers of educational institutions have begun to focus more closely on this topic. In the present study, it was observed that for faculty development to be effective, the educator must have a desire to learn; however, institutional support and recognition are also essential. Faculty Development Programs must be flexible and adaptable, to meet the needs of the institution and its professors, and encourage reflection on their practices, though the exchange of experiences, the development of interpersonal relationships, and collaboration. However, it is vital to identify and facilitate the development of leadership skills, and to systematically evaluate the process and the results achieved. This will encourage teachers to develop in their academic careers and thereby increase the professionalization of teaching. Managers and teachers can sustain a shared mission to win resources, adapt to change, strive for excellence in the leadership of the organization in a national and international context, and consequently, provide a quality medical education.